Colour formation on the wings of the butterfly Hypolimnas salmacis by scale stacking - Siddique, Radwanul Hasan; Bartels, Carolin; Wacker, Irene (Scientific reports, 2016)
The butterfly genus Hypolimnas features iridescent blue colouration in some areas of its dorsal wings. Here, we analyse the mechanisms responsible for such colouration on the dorsal wings of Hypolimnas salmacis and experimentally demonstrate that the lower thin lamina in the white cover scales causes the blue iridescence. This outcome contradicts other studies reporting that the radiant blue in Hypolimnas butterflies is caused by complex ridge-lamellar architectures in the upper lamina of the cover scales. Our comprehensive optical study supported by numerical calculation however shows that scale stacking primarily induces the observed colour appearance of Hypolimnas salmacis.
Gesehen am 07.05.2020